PENGARUH DIMENSI PENGETAHUAN MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA PELANGGAN SITUS ONLINE SHOPEE.CO.ID DI KOTA KENDARI - Nasrul Nasrul (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2020)
This study aims to explain and empirically test the effect of the Brand Knowledge Dimensions on Purchasing Decisions of Shopee.Co.Id Online Sites in Kendari City. The sampling technique used is accidental sampling, which is a sample determination technique based on coincidence, ie anyone who accidentally meets a researcher can be used as a sample if it is seen by someone who happens to match the data source. The sample in this study was 96 respondents. The data analysis method used is quantitative descriptive. The analytical tool used is multiple linear regression. The results of this study stated that: simultaneous brand knowledge including brand awareness and brand image significantly influence Purchasing Decisions on Shopee.Co.Id Online Site Customers in Kendari City.